2001
DOI: 10.1128/aac.45.8.2405-2405.2001
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Metabolites of the Human Immunodeficiency Virus Protease Inhibitor Nelfinavir in Humans: Structural Identification, Levels in Plasma, and Antiviral Activities

Abstract: Page 1090, column 1, lines 1 to 5: "did not show any. .. or its metabolites" should read "showed no significant differences in exposure to either the parent drug or its metabolites between the first dose and steady state (Table 3); however, this analysis was not designed or powered to rule out modest changes in clearance or exposure, and the trend for increased M8-to-nelfinavir concentration ratio on day 28 may reflect modest induction of metabolism during multiple dosing."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 0 publications
1
41
1
Order By: Relevance
“…No data are available for inhibition of SARS-CoV-2 replication by the M8 metabolite but if active, this could provide and advantage for nelfinavir over tipranavir for COVID-19. Conversely, While the analysis of pharmacokinetics relative to potency of these molecules against SARS-CoV-2 is encouraging, it should be noted that the reported in vitro activity for HIV [58,65] is far higher than that against SARS-CoV-2 and both drugs are highly protein bound [66,67]. While older HIV protease inhibitors like tipranavir and nelfinavir are associated with long-term toxicities [58,[68][69][70] these may be less of a concern over shorter term exposure if they prove to be successful for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…No data are available for inhibition of SARS-CoV-2 replication by the M8 metabolite but if active, this could provide and advantage for nelfinavir over tipranavir for COVID-19. Conversely, While the analysis of pharmacokinetics relative to potency of these molecules against SARS-CoV-2 is encouraging, it should be noted that the reported in vitro activity for HIV [58,65] is far higher than that against SARS-CoV-2 and both drugs are highly protein bound [66,67]. While older HIV protease inhibitors like tipranavir and nelfinavir are associated with long-term toxicities [58,[68][69][70] these may be less of a concern over shorter term exposure if they prove to be successful for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data in animal studies have not demonstrated any fetal toxicity of this agent [6]. NFV is mainly metabolized by cytochromes P450 (CYP) 3A4 and 2C19 [7], whose metabolic activity has been shown to be altered during pregnancy, which, together with the physiological changes in gastrointestinal motility, volume of distribution and hepatic blood flow, may significantly affect the pharmacokinetics of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of the equally active hydroxy-t-butylamidenelfinavir metabolite (M8) is mediated exclusively by CYP2C19, with further metabolism by CYP3A4 after its formation. 7,8 Previous studies have shown that CYP3A4 and CYP2C19 activity may be altered during pregnancy, and this alteration may potentially affect the pharmacokinetics of nelfinavir and M8 in pregnant women. 9,10 In addition to altered activity of certain hepatic enzymes, other physiologic changes that occur during pregnancy have the potential to influence drug disposition (eg, altered gastrointestinal motility, increased total body water and fat, increased cardiac output, and reduced serum albumin; for review see reference 11).…”
mentioning
confidence: 99%